PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG - Faishal, Muhammad; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to analyze the internal factors that affect audit report lag of financial reports to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are board size, board independence, audit committee, and audit committee meetings as the independent variable, while the audit report lag as the dependent variable.The sample consists of 292 companies listed in the Indonesia Stock Exchange (IDX)period 2012-2014. The data that was used in this research was secondary data and selected by using purposive sampling method. This study used purposive sampling method and multiple linear regression as the analysis method. Before being conducted by regression test, it was examined by using the classical assumption tests.The results of this study indicate that the committee audit size did not have significant influence to the audit report lag. Board size, independence board and audit committee meetingshave significant influence to audit report lag.